Language and Identity in Ukraine: Was it Really Nation-Building? - Polese, Abel (Studies of Transition States and Societies, 2011)
After the collapse of three socialist federations in Eastern Europe, the expression ‘nation-building’ returned to the heart of academic debates. Like other former socialist republics, Ukraine has started its nationbuilding project trying to balance between a limitation of centrifugal forces and the ‘nationalisation’ (Brubaker 1994) of the state. This article examines the main features of language policies within the Ukrainian nation-building project and adopts a dual approach. It ﬁ rst surveys the political will that has been incarnated in language policies since 1991, and how national identity has been aﬀ ected by those policies. However, it counterpoises this approach with an analysis of bottom actors and their attitude towards language policies. The framework constructed is intended to question the idea that nation-building is mainly an elite driven process and to suggest that common people can participate in a political project by renegotiating its features at the local level.